THE BLOW-UP SOLUTIONS OF THE HEAT DISSIPATION EQUATION WITH NONLINEAR BOUNDARY FLUX - Begulov U. U.; Abduraimov O. Sh. (Journals Park Publishing, 2024)
In this paper, we investigate the boundary problem for the doubly nonlinear heat dissipation equation. We also use the self-similar solution construction method to solve the problem.Global or blow-up theorems of the solution are proved.
Keywords: Blow-up, global, density, self-similar solution, mathematical modeling.